The effects of induced variability in the performance on shot in soccer - Garcia-Herrero, J. A.; Sanchez-Sanchez, J.; Luis-Pereira, J. M.; Menayo, R. (International Journal of Sports Science & Coaching, 2016)
The effects of induced variability in the improvement on shot at goal in soccer were examined. The hypothesis tested was that induced variability would be more beneficial for performance than repetition practice; 20 young soccer players (N=20) trained with induced variability, and 21 (N=21) trained with repetition method. Accuracy and ball speed were analyzed in three moments: pre-test, post-test carried out after 10 training sessions and re-test, applied at short term (one week). The induced variability group improved the accuracy on post-test (p=0.005) and re-test (p=0.0001). The repetition training group improved the accuracy on re-test (p=0.0001). The ball speed increased in both groups on post-test and re-test (p=0.0001). The induced variability improves the accuracy of the kicks at end of training, and short term after periods without practice. The repetition practice is effective to perform after no practice time only. The practice in both conditions leads to an increase in the ball speed at end of training as after periods without practice. ABSTRACT FROM AUTHOR